EVALUACIÓN IN VITRO DE LA CAPACIDAD ANTIMICROBIANA DE EXTRACTOS ETANÓLICO Y ACUOSO DE LA CÁSCARA DE PLÁTANO (Musa paradisiaca), FRENTE A Escherichia coli Y Salmonella - ALEJANDRO SUAREZ, DARWIN JAVIER (2025)
The present research evaluated in vitro the antimicrobial capacity of ethanolic and aqueous extracts of ripe plantain peel (Musa paradisiaca) against Escherichia coli and Salmonella, the thesis explores the valorization of this agroindustrial by-product rich in polyphenols and other bioactive compounds